Eating habits and attitudes of mothers of children with non-organic failure to thrive. - McCann, J; Stein, A; Fairburn, C; Dunger, D (1994)
The eating habits and attitudes concerning body shape and weight among 26 mothers of children with non-organic failure to thrive (the index group) were studied using the eating disorder examination. They were compared with equivalent data on 26 individually matched women who participated in a large community survey. The index mothers' views of their child's weight and shape were also studied. The principal findings were, firstly, that when compared with the comparison group, mothers of children with non-organic failure to thrive had higher levels of dietary restraint. Secondly, despite their child's low weight, 50% of the index mothers were restricting their child's intake of 'sweet' foods, and a further 30% were restricting foods they considered 'fattening' or 'unhealthy'. These results raise the question of whether maternal eating habits and attitudes have a causal role in the genesis of non-organic failure to thrive. They suggest that careful inquiry about the mothers' eating habits and attitudes is needed when assessing children with non-organic failure to thrive.